Strategic Intervention dalam Bimbingan Klasikal untuk Mengatasi Kesulitan dan Meningkatkan Fokus Belajar - Lila Kurniawati; Vivi Rahmawati; Nining Solekah (CV. ITTC INDONESIA, 2025)
This study aims to improve the learning focus of seventh-grade students at SMP Negeri 4 Kediri through classroom guidance services using the Strategic Intervention approach. The research employed a Classroom Action Research (CAR) design based on Kemmis & McTaggart’s model in two cycles. Cycle I implemented an interactive lecture method, while Cycle II applied educational cinema. The subjects were 32 students. Data were collected through observation, interviews, and student reflections in worksheets (LKPD), then analyzed descriptively and qualitatively. The findings showed an improvement in students’ learning focus from 60% in Cycle I to 80% in Cycle II. The improvement was evident in four aspects: attention, participation in discussions, comprehension of material, and application of learning strategies. These results confirm that classroom guidance services using the Strategic Intervention approach are effective in enhancing students’ learning focus.